1999
DOI: 10.1902/jop.1999.70.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Caffeine and Prostaglandin E2 on the Proliferation of Osteoblast‐Like Cells (UMR106‐01)

Abstract: The present data for the first time demonstrate the possible implication of routine caffeine intake in the acceleration of pathological conditions of periodontitis. Thus, we propose that chronic caffeine intake is one of the possible risk factors in the advancement of pathology in the periodontitis patient. Further research in this area is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 14 publications
5
47
1
2
Order By: Relevance
“…Possibly in CAF group there was greater plasma concentration of caffeine compared to the CO group, consequently higher bioavailability during the healing process after tooth extraction. This increased supply in the repair site possibly led to changes in intracellular mediators and thus to a lower viability and activity of osteoblasts to synthesize bone matrix, as evidenced in several studies (8,20,21), and also higher osteoclastic activity (19), which may have provided low maturity of bone trabeculae with the use of pure caffeine (Figs. 1F, I).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possibly in CAF group there was greater plasma concentration of caffeine compared to the CO group, consequently higher bioavailability during the healing process after tooth extraction. This increased supply in the repair site possibly led to changes in intracellular mediators and thus to a lower viability and activity of osteoblasts to synthesize bone matrix, as evidenced in several studies (8,20,21), and also higher osteoclastic activity (19), which may have provided low maturity of bone trabeculae with the use of pure caffeine (Figs. 1F, I).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that caffeine, a major constituent of coffee, is associated with a significantly increased risk of fractures, osteoporosis, periodontal disease and poor osseointegration of bone grafts (8,9,12). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a significant effect of caffeine on alkaline phosphatase activity was observed at 1 mM dose. Earlier studies on caffeine on osteoblast growth [19,23] have used caffeine doses in the range of 0.1-0.4 mM; while studies of caffeine on the release of intracellular calcium have used much higher concentrations of caffeine (4 and 10 mM) [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, coffee must be a useful beverage for health. In contrast, some inves tigators have reported that caffeine and/or heavy coffee intake may serve as risk factors for lifestyle-related dis eases including heart disease and osteoporosis as well as periodontal diseases (3,4), which are intimately as sociated with nutrition, exercise, alcohol, smoking, and several other lifestyle factors. In the present study, we investigated a relationship between coffee and fitness; namely, the effects of coffee intake on body weight gain and serum cholesterol, cytokine and activities of GOT or GPT levels in lipopolysaccharide (LPS)-injected rats.…”
mentioning
confidence: 98%